Preparation of waste-based Cu–Cu2O/SiO2 photocatalyst from serpentine tailings and waste printed circuit boards and photoreduction of Cr(VI). Issue 8 (15th April 2023) - Zhu, Ping; Li, Yuan; Bilal; Ma, Yi; Ruan, Xiuxiu; Zhang, Qianzhi
Abstract: In China, a large amount of serpentine tailings and waste printed circuit boards (WPCBs) are produced every year. Serpentine tailings contain about 43% SiO2 and WPCBs contain about 20% Cu. Reusing their resources can not only solve the problem of environmental pollution, but also produce certain economic benefits. In this study, waste-based SiO2 support, waste-based Cu–Cu2 O and Cu–Cu2 O/SiO2 photocatalyst were prepared using serpentine tailings and WPCBs as Si and Cu sources. The waste-based SiO2 of 750 nm particle size was obtained by precipitation of 0.7 mol/L Na2 SiO3 solution from the serpentine tailings and its specific surface area reached 57.72 m 2 /g after 600 °C calcination. Cu and the waste-based Cu–Cu2 O were loaded on the waste-based Cu2 O and SiO2 support, respectively, and the phase structure of the catalysts has not changed by the characterization of SEM, XRD and XPS. The activity of the photocatalytic reduction of Cr (VI) with the waste-based catalysts showed in the following order: Cu2 O < Cu2 O/SiO2 2 O < Cu–Cu2 O/SiO2, inferring by the investigation of photoelectric properties that Cu prevented the recombination of Cu2 O electron-hole pairs, the Cu–Cu2 O dispersed on SiO2 support surface to obtain a higher specific surface area. The waste-based Cu–Cu2 O/SiO2 photocatalyst showed no obvious deactivation after 5 cycles. The mechanism revealed that photogenerated electrons are the major reactive species for the photodegradation of Cr (VI). The study indicates that the waste-based Cu–Cu2 O/SiO2 is potentially a developed, low-cost catalyst from sustainable resources. The production of Cu–Cu2 O/SiO2 photocatalyst by using WPCBs and serpentine tailings represents the potential usage of waste into valuable material. Graphical abstract: Image 1